Defects in the implementation of Industrialised Building System (IBS) for residential PPR housing in Seri Iskandar Perak / Ibrahim Mohd Soofie and Mohd Nazri Abdullah - Mohd Soofie, Ibrahim; Abdullah, Mohd Nazri (2023)
Industrialized Building Systems (IBS), or prefabrication, involves off-site manufacturing of components for easy installation. However, IBS faces challenges in Malaysia due to inadequate risk management, resulting in common failures. This paper objectives are to identify the types of defects and to analyze the causes of defects in the IBS project at PPR Seri Iskandar, Perak housing. Questionnaires from 80 residents were analyzed, revealing roof leaks as the primary defect. Interestingly, residents expressed high satisfaction with the quality of the house space. The findings also indicated that natural phenomena were the main contributors to defects in PPR Seri Iskandar. To enhance long-term satisfaction, it is recommended for housing developers and contractors to prioritize higher-quality materials in IBS projects.